Analysis of Gap Between Green Purchase Intention and Green Purchase Behavior a Case Study of Vietnamese Students - Thuy Huynh, Tien Chau; Ngoc Ton, Han Nu; Nhu Ngoc, Nguyen Huyn (NIDA Development Journal, 2025)
Why do people say they want green products, but they do not tend to buy them? This phenomenon is known as green gap. Image Research Theory and Motivation-Opportunity-Ability Theory were used to build up the conceptual framework reflecting sequencing relationships from green purchase intention, implementation intention, to green purchase behavior with two moderators (e.g., action self-efficacy, coping self-efficacy). Online questionnaires were distributed to respondents (i.e., Facebook users and university students) with their preferential purchase, experiences and involvement in green products. A total of 233 valid cases was collected for theoretical estimation by using partial least squares structural equation modelling. It reveals significant sequencing relationships among green purchase intention, implementation intention, and green purchase behavior with positive impacts. It may bring theoretical implication on green gap in Vietnam context, and practical implications to encourage sustainable consumption among younger generation.